Basic moral philosophy - Holmes, Robert L. (Wadsworth, 2003)
Striving for a comprehensiveness that is rare in introductory ethics texts, BASIC MORAL PHILOSOPHY introduces students without prior backgrounds in ethics to a clear and systematic approach to ethical theories. Illustrating the historical roots of ethical theories and placing individual theories in the broader context of moral philosophy's basic problems, the text presents reasoned assessments of various theories in order to help students actively engage the material and develop their own views. This versatile book can be used in a number of different fashions: as a core text in any introductory ethics course, as a short introductory section on ethical theory at the beginning of a problems course or other courses in applied ethics (e.g., bioethics), as the ethics component of an introduction to philosophy course, or finally, as a supplementary review text for more advanced undergraduates and graduate students.